2017
DOI: 10.1155/2017/5482768
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Tumor-Associated Macrophages (TAM) Phenotype by Platelet-Activating Factor (PAF) Receptor

Abstract: Platelet-activating factor (PAF) plays an important role in the pathogenesis of several types of tumors. The biological effects of PAF are mediated by the PAF receptor (PAFR), which can be expressed by tumor cells and host cells that infiltrate the tumor microenvironment. In the present study, we investigated the role of PAFR expressed by leukocytes that infiltrate two types of tumors, one that expresses PAFR (TC-1 carcinoma) and another that does not express the receptor (B16F10 melanoma) implanted in mice th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…We found that two types of murine tumors, B16F10 melanoma and TC-1 carcinoma, showed significantly less growth in mice genetically deficient for PAFR (PAFRKO) than in wild type (WT) mice. This change occurred in parallel with the increased frequency of neutrophils and CD4 + /CD8 + lymphocyte infiltration in the tumors implanted in PAFRKO, suggesting that PAFR may be involved in the recruitment of these cells into the tumor stroma 38 . Macrophages undergo functional and phenotypic changes in response to signals from the tumor microenvironment.…”
Section: Pafr and The Tumor Microenvironmentmentioning
confidence: 74%
See 1 more Smart Citation
“…We found that two types of murine tumors, B16F10 melanoma and TC-1 carcinoma, showed significantly less growth in mice genetically deficient for PAFR (PAFRKO) than in wild type (WT) mice. This change occurred in parallel with the increased frequency of neutrophils and CD4 + /CD8 + lymphocyte infiltration in the tumors implanted in PAFRKO, suggesting that PAFR may be involved in the recruitment of these cells into the tumor stroma 38 . Macrophages undergo functional and phenotypic changes in response to signals from the tumor microenvironment.…”
Section: Pafr and The Tumor Microenvironmentmentioning
confidence: 74%
“…Moreover, when we analyzed the macrophages infiltrated in the tumors on day 15, the PAFKO mice had a higher frequency of M1-like macrophages (CD11c + ; high iNOS; low arginase; low IL10) than WT mice, whereas those from WT mice presented the M2 phenotype marker (CD206 + ). Thus, in the absence of PAFR, the tumor infiltrating macrophages acquire an activated phenotype, which is associated with the reduced tumor growth observed in PAF KO animals 38 , suggesting that PAFR activation reprograms macrophages towards the M2 phenotype in experimental tumors.…”
Section: Pafr and The Tumor Microenvironmentmentioning
confidence: 96%
“…Histamine (H 1 and H 2 receptors) [30], cysteinyl leukotriene D 4 (LTD 4 ) [31], platelet-activating factor (PAF) [32], and vascular endothelial growth factor A (VEGF-A) [33] modulate the functions of monocytes. Mast cells interact with macrophages through the release of histamine (H 1 , H 2 , and H 3 receptors) [34, 35], IL-6 [36], IL-13 [37], PGD 2 [38], and PAF [32]. PGD 2 [39], PGE 2 [40], VEGF-C [41], and histamine (H 1 and H 2 ) [42, 43] influence the activity of dendritic cells.…”
Section: Mast Cells In the Homeostasis Of The Immune Systemmentioning
confidence: 99%
“…The stability of PAF-R agonists is regulated by PAF metabolizing enzymes, PAF-acetyl hydrolases (PAF-AH), which are found in multiple cell types and lipoproteins [ 3 , 4 ]. Studies, including ours, have shown that enzymatic (i.e., PAF) or non-enzymatically (e.g., ultraviolet B (UVB), cigarette smoke, jet fuel, and tumor promoters, such as PMA) generated PAF-R agonists mediate various pathophysiological effects, including enhanced growth of tumors in experimental models [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In particular, tumor growth promoting effects can be mimicked by the administration of a non-metabolizable form of PAF (1-hexadecyl-2- N -methyl carbamoyl glycerophosphocholine (CPAF)) [ 7 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the intriguing roles of PAF-R agonists in modulating the growth of experimental melanoma and NMSC in response to diverse stimuli [ 7 , 15 , 19 , 23 , 24 , 25 , 26 ], the current study was designed to determine if systemic PAF-R agonist exposure modulates DMBA/PMA-induced cutaneous carcinogenesis. Our study took advantage of a recent report by Nasti et al, which characterized a DMBA/PMA cutaneous carcinogenesis model [ 27 ] in C3H/HeN mice that induces both NMSC and melanocytic nevi, which in turn can be transformed into malignant melanoma [ 28 ].…”
Section: Introductionmentioning
confidence: 99%